(untitled) (Bangladesh Journal of Animal Science, 2012)
The experiment was conducted to evaluate the bull performance based on semen quality and 60 days non-return rate. Data were collected from 60 ejaculates and 525 services. Semen for insemination was used from bulls of different genetic groups (2 Holstein cross, 1 Sindhi cross, 1 Sahiwal cross and 1 Red Chittagong). Individual bull effect was found to be significant (P<0.01) on volume per ejaculate, mass motility, sperm concentration, live sperm and normal sperm percentage. The significantly (P<0.01) highest volume per ejaculate, sperm concentration, live sperm and normal percentage were found in Holstein cross and lowest in Red Chittagong Bull. Non-return rate was highest in Holstein cross bull and lowest in Red Chittagong Bull. Significant (P<0.01) positive correlation was observed in mass motility, live sperm and normal sperm percentage with non-return rate. It was concluded that Holstein cross Bull was the best among the bulls. DOI: http://dx.doi.org/10.3329/bjas.v37i2.9875 BJAS 2008; 37(2): 1-7